2007
DOI: 10.1073/pnas.0611470104
|View full text |Cite
|
Sign up to set email alerts
|

Proteorhodopsin photosystem gene expression enables photophosphorylation in a heterologous host

Abstract: Proteorhodopsins (PRs) are retinal-containing proteins that catalyze light-activated proton efflux across the cell membrane. These photoproteins are known to be globally distributed in the ocean's photic zone, and they are found in a diverse array of Bacteria and Archaea. Recently, light-enhanced growth rates and yields have been reported in at least one PR-containing marine bacterium, but the physiological basis of light-activated growth stimulation has not yet been determined. To describe more fully PR photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
200
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(203 citation statements)
references
References 37 publications
1
200
0
1
Order By: Relevance
“…PRs have also been heterologously expressed in non-photosynthetic hosts (5,(21)(22)(23)(24)(25). For example, the introduction of a PR in Shewanella oneidensis increased the pmf, which resulted in increases in electrical current generation, lactate uptake, and survival under starvation conditions (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRs have also been heterologously expressed in non-photosynthetic hosts (5,(21)(22)(23)(24)(25). For example, the introduction of a PR in Shewanella oneidensis increased the pmf, which resulted in increases in electrical current generation, lactate uptake, and survival under starvation conditions (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the introduction of a PR in Shewanella oneidensis increased the pmf, which resulted in increases in electrical current generation, lactate uptake, and survival under starvation conditions (23,24). In Escherichia coli, the pmf generated by a PR resulted in ATP synthesis (22), was able to drive the flagellar motor (21), and could be used to significantly increase the production of hydrogen by a co-introduced hydrogenase (25,26). Very recently, functional expression of a proteorhodopsin in E. coli was shown to cause a minute increase the growth rate of this organism when growing fermentatively (27).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodopsin proteins are documented to contribute to similar pigmentation in other rhodopsin-expressing organisms (Bolhuis et al, 2006;Gomez-Consarnau et al, 2007). Alternatively, such coloration is often caused by the presence of carotenoid pigments (Trutko et al, 2005), which increases the probability that these organisms carry rhodopsin genes, because the retinal chromophore of these photoproteins is a byproduct of carotenoid biosynthesis (Martinez et al, 2007).…”
Section: Isolate Mwh-uga1 Encodes An Lg1-actrmentioning
confidence: 99%
“…Proteorhodopsins (PRs) (Béjà et al, 2000(Béjà et al, , 2001 are bacterial retinal-binding membrane pigments that belong to the microbial rhodopsin superfamily (Spudich et al, 2000) and are predicted to have an important role in supplying light energy for microbial metabolism in marine ecosystems (Béjà et al, 2000(Béjà et al, , 2001Sabehi et al, 2005;Martinez et al, 2007;Walter et al, 2007). PRs have been observed in different ocean regions (Béjà et al, 2000(Béjà et al, , 2001de la Torre et al, 2003;Man et al, 2003;Sabehi et al, 2003Sabehi et al, , 2004Sabehi et al, , 2005Venter et al, 2004;Frigaard et al, 2006) and are found in diverse taxonomic backgrounds, including the ubiquitous marine gammaproteobacterial SAR86 (Béjà et al, 2000;Sabehi et al, 2004Sabehi et al, , 2005 and alphaproteobacterial SAR11 (Giovannoni et al, 2005a, b;Sabehi et al, 2005) groups, as well as in marine Bacteroidetes (Venter et al, 2004;Gó mez-Consarnau et al, 2007), planktonic Archaea (Frigaard et al, 2006) and other microbial taxa (de la Torre et al, 2003;Sabehi et al, 2003Sabehi et al, , 2005Venter et al, 2004;McCarren and DeLong, 2007).…”
Section: Introductionmentioning
confidence: 99%